METHOD OF CLASSIFICATION OF IMPACT IMPULSES IN DIAGNOSIS OF COMPOSITE MATERIALS - Бабак, В. П.; Єременко, В. С.; Мокійчук, В. М. (Proceedings of National Aviation University (archive), 2021)
The method of constructing the space of classification features on the basis of the distribution of shock pulses on orthogonalized reference signals is considered. The advantages of using this method in the classification of defects in composite materials are shown.